2010
DOI: 10.1103/physrevb.82.100412
|View full text |Cite
|
Sign up to set email alerts
|

Local moments and symmetry breaking in metallic PrMnSbO

Abstract: We report a combined experimental and theoretical investigation of the layered antimonide PrMnSbO which is isostructural to the parent phase of the iron pnictide superconductors. We find linear resistivity near room temperature and Fermi liquid-like T^{2} behaviour below 150 K. Neutron powder diffraction shows that unfrustrated C-type Mn magnetic order develops below \sim 230 K, followed by a spin-flop coupled to induced Pr order. At T \sim 35 K, we find a tetragonal to orthorhombic (T-O) transition. First pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
66
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 19 publications
(30 reference statements)
12
66
0
5
Order By: Relevance
“…a C-type structure, in which the in-plane Mn spins are antiferromagnetically aligned as in BaMn 2 As 2 , but with the ordered moment in the ab-plane instead of in the c-axis direction, and with ferromagnetic instead of antiferromagnetic alignment between layers. 497 The compound undergoes a tetragonal to orthorhombic transition below 35 K, and the ordered moments at 4 K are 3.69(3) µ B /Mn, similar to that of Mn in BaMn 2 As 2 , and 2.96(3) µ B /Pr. Compounds based on Sr 2 Mn 3 As 2 O 2 are bodycentered-tetragonal (I 4/mmm) with a = 4.14Å and c = 18.82Å for Sr 2 Mn 3 As 2 O 2 and with 2 f.u./unit cell.…”
Section: 165mentioning
confidence: 83%
“…a C-type structure, in which the in-plane Mn spins are antiferromagnetically aligned as in BaMn 2 As 2 , but with the ordered moment in the ab-plane instead of in the c-axis direction, and with ferromagnetic instead of antiferromagnetic alignment between layers. 497 The compound undergoes a tetragonal to orthorhombic transition below 35 K, and the ordered moments at 4 K are 3.69(3) µ B /Mn, similar to that of Mn in BaMn 2 As 2 , and 2.96(3) µ B /Pr. Compounds based on Sr 2 Mn 3 As 2 O 2 are bodycentered-tetragonal (I 4/mmm) with a = 4.14Å and c = 18.82Å for Sr 2 Mn 3 As 2 O 2 and with 2 f.u./unit cell.…”
Section: 165mentioning
confidence: 83%
“…Various studies of the parent LnMnP nO have shown that the MnP n planes are universally antiferromagnetic [3][4][5][6][7][8][9][10] with in-plane checkerboard magnetic structure similar to the in-plane magnetic ordering in the various Mn-122 compounds. For compounds with moment-bearing rare-earth ions (Ln), a second low temperature magnetic ordering of the rare-earth element (i.e., Ce, Nd, and Pr) accompanied by a Mn-spin reorientation transition have been observed [4][5][6][7][8][9]. Other Mn-1111 compounds with variations on the Ln or P n sites have also been shown to order with the same in-plane * yliu@ameslab.gov AFM structure, albeit with uniform or alternate stacking of the AFM planes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the spin reorientation transition in the square lattice of Mn ions is apparently related to the presence of f moments above and below the Mn lattice, because it exists in neither LaMnAsO nor BaMn 2 As 2 6,9) but in NdMnAsO and PrMnSbO [7][8][9] and probably in CeMnAsO. We have recently 9 studied another related compound, CeCrAsO, and observed a very similar transition at 36 K in magnetic susceptibility and heat capacity, which may be due to a spin reorientation transition.…”
mentioning
confidence: 99%
“…[7][8][9] However, the temperature evolution of the Nd/Pr moments reported is quite unusual: for Nd, a steep increase at 25-20 K is followed by a gradual increase to a saturation at approximately 4 K. 7) This suggests that the moments are generated by the internal field from the reoriented Mn moments and that Nd/Pr moments also undergo parasitic spins in the present family of compounds are an interesting topic for investigation in our future work, 18) and should be sufficiently strong to generate sizable internal fields at the f-spin site and to overcome the geometrical frustration.…”
mentioning
confidence: 99%